Social Return and Financing of Urban Regeneration Policies - Iluminada Fuertes; David Cabedo (European Regional Science Association (ERSA), 2011)
This paper analyses an alternative measurement framework capable of capturing the return on investment of urban regeneration projects through a cost-benefit analysis. Financial returns on investment are calculated as the ratio between the benefits accruing from the performance of a given project and the funds involved in their implementation. Both, benefits and funds, must be named in monetary terms. However in urban regeneration projects, due to their dual economic and social nature, is more difficult to quantify the profits generated because most of them are subjective (greater quality of life, better community welfare, etc.). There is a wide array of value taking place in a urban regenerative process (economic value, blended value, social value) some of which are measurable in a traditional Investment/Return framework (with its implicit economic returns assumption) and more of which are not so that they remain partially hidden from stakeholders. Based on the foregoing, the purpose of this study is twofold: to go deeply on the cost-effectiveness ratio of urban regeneration projects through consideration of social impacts and to analyze some new alternative funding formulas that arise particularly in a time of financial constraint. The papers argues that the SROI (Social Return On Investment) method appears as the most appropriate measurement tool to capture the full public benefit as well as the Tax Increment Financing and the Joint European Support for Sustainable Investment in City Areas -Jessica, seem to be two innovative financing formulas based on a market approach.
Keywords: 330